The Foreign Commission of the Soviet Writers’ Union in 1950s-1960s: Boundaries, Obstacles, Tricks, Embarrassment, Impact - Kristina Buynova (eSamizdat)
In the 1950s and 1960s, the Foreign Commission of the Soviet Writers’ Union occupied the niche of mediator in relations between Western literature and the USSR. It was essentially a propaganda institution that inherited the traditions of MORP and VOKS. This alone suggests an active, perhaps even aggressive, style of recruiting among foreign writers. In this article I will show that the reality was different. Party patronage and the constant manipulation of the ‘rules of the game’ excluded any proactivity on the part of the Commission. Although the aim of the Foreign Commission was to ‘broaden contacts’, it tended to concentrate on strengthening existing ones. In selecting new contacts, the FC relied on the assessments of translators, writers and critics rather than on party preferences, and then presented itself as a ‘progressive’ entity. The visit of the latter would become a kind of consummation of the relationship. The FC was keen to please its guests, so any awkward situations were carefully smoothed over by the consultants, or ‘minders’, as the foreigners called them. There could be no official instructions, but a number of tricks and stratagems – evasion, stalling, shifting attention, citing temporary circumstances – were more or less clear to the staff.